Meje spreminjanja opisa kaznivega dejanja iz obtožnega akta v sodbi - Briški, Lora (Pravnik, 2025)
A corollary of the accusatorial principle (Article 19 of the Criminal Procedure Act – CPA) is the requirement of objective identity between the charge and the judgment (Article 354 of the CPA). This requirement mandates that the judgment may be based solely on the act described by the prosecutor in the indictment. The significance of this requirement is twofold. First, by limiting the court’s judgment to the act charged by the prosecutor, it preserves the separation between the procedural functions of charging and deciding on the charge, which is essential for ensuring an impartial trial. Second, it allows the accused to organise their defence based on a specific charge brought against them. If the court were to convict the accused of a different offence, it would deprive them of the opportunity to organise an appropriate defence. In this article, I examine whether a court that perceives an act differently during the trial from how the prosecutor described it in the indictment may adjust the description without overstepping into the prosecution’s role. I explore this question by considering the insights of Slovenian legal theory and by analysing case law that interprets the requirement of objective identity between the charge and the judgment in specific cases.
Keywords: accusatorial principle; identiteta obtožbe in sodbe; identity of the charge and the judgment; ločitev procesnih funkcij; modification of the description of the offence; objective identity; objektivna identiteta; obtožno načelo; pravica do seznanitve z obtožbo; right to be informed of the accusation; separation of procedural functions; sprememba opisa kaznivega dejanja